2020
DOI: 10.31234/osf.io/3utpv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentence processing: How words generate syntactic structures in the brain

Abstract: Language comprehension relies on the fundamental ability to create meaningful syntactic structures from single words during on-line processing. Time-resolved neuroimaging techniques can be used to measure electrophysiological activity revealing the neural dynamics underpinning these combinatorial processes in the brain. In the present chapter, we review and critically evaluate studies that have specifically investigated the electrophysiological bases of sentence-level syntactic processing using different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 105 publications
(219 reference statements)
0
14
0
Order By: Relevance
“…Because local information processing in the brain, as well as interactions between areas, are often characterized by frequency specific activity (brain oscillations or rhythms) (see below), we performed source localized time‐frequency analysis on the acquired MEG data. Accumulated evidence assigns brain rhythms in different frequency bands to various processes related to the language domain (for reviews, Bastiaansen & Hagoort, 2006 ; Maguire & Abel, 2013 ; Meyer, 2018 ; Murphy & Benítez‐Burraco, 2019 ; Prystauka & Lewis, 2019 ; Martorell, Morucci, Mancini, & Molinaro, 2020 ). For instance, the gamma band (>30 Hz) has been reported to reflect syntactic structure building (Ding, Melloni, Zhang, Tian, & Poeppel, 2016 ; Nelson et al, 2017 ) or, more generally, sentence‐level information composition (see Martorell et al, 2020 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because local information processing in the brain, as well as interactions between areas, are often characterized by frequency specific activity (brain oscillations or rhythms) (see below), we performed source localized time‐frequency analysis on the acquired MEG data. Accumulated evidence assigns brain rhythms in different frequency bands to various processes related to the language domain (for reviews, Bastiaansen & Hagoort, 2006 ; Maguire & Abel, 2013 ; Meyer, 2018 ; Murphy & Benítez‐Burraco, 2019 ; Prystauka & Lewis, 2019 ; Martorell, Morucci, Mancini, & Molinaro, 2020 ). For instance, the gamma band (>30 Hz) has been reported to reflect syntactic structure building (Ding, Melloni, Zhang, Tian, & Poeppel, 2016 ; Nelson et al, 2017 ) or, more generally, sentence‐level information composition (see Martorell et al, 2020 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence assigns brain rhythms in different frequency bands to various processes related to the language domain (for reviews, Bastiaansen & Hagoort, 2006 ; Maguire & Abel, 2013 ; Meyer, 2018 ; Murphy & Benítez‐Burraco, 2019 ; Prystauka & Lewis, 2019 ; Martorell, Morucci, Mancini, & Molinaro, 2020 ). For instance, the gamma band (>30 Hz) has been reported to reflect syntactic structure building (Ding, Melloni, Zhang, Tian, & Poeppel, 2016 ; Nelson et al, 2017 ) or, more generally, sentence‐level information composition (see Martorell et al, 2020 for a recent review). Recent intercranial measurements in language related regions of the left hemisphere (Nelson et al, 2017 ) showed that high gamma power gradually increases when reading sentences word by word, until it suddenly drops when the words can be merged into a phrase (phrase closure).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, as Murphy argues, neural oscillations exhibit algorithmic-like temporal sensitivity, making them the perfect candidate to explain WHEN and HOW language operations dynamically manifest in brain regions. Going beyond the more traditional analyses of electrophysiological signals such as event-related potentials, current neurolinguistic research is increasingly focused on neural oscillations (for a recent review in the context of syntactic processing, see Martorell et al 2020). Murphy critically examines a broad range of cognitive neuroscience findings on neural oscillations, considering various types of electrophysiological studies on language (single-word, sentence-level comprehension, etc.…”
mentioning
confidence: 99%
“…It is critical to note that syntax and semantics are certainly intertwined (e.g. structure and meaning correlate with each other to a considerable extent), and this makes it extremely challenging to tease them apart in any experiment (for further discussion, see Pylkkänen 2019, Martorell et al 2020. Moreover, a certain amount of evidence allegedly supporting Murphy's model comes from studies that have conflated syntactic and semantic aspects in their experimental manipulations (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation